SPRC Suppresses Experimental Periodontitis by Modulating Th17/Treg Imbalance - Peng, Qian; Zhao, Bingkun; Lin, Jie; Liu, Haixia; Zhou, Rong; Lan, Dongmei; Yao, Chao; Cong, Shaohua; Tao, Shen; Zhu, Yizhun; Wang, Raorao; Qi, Shengcai (Frontiers in Bioengineering and Biotechnology, 2022)
Object: The aims of the study were to explore the protective effects of S-propargyl-cysteine(SPRC) on periodontitis and to determine the underlying mechanisms. Methods: A rat periodontitis model was constructed by injecting LPS and SPRC (0, 25, 50 mg/kg/d) was administered intraperitoneally. H2S and CSE level were detected. The alveolar bone level was evaluated by micro-CT, HE staining and methylene blue staining analysis. Inflammation-related factors, Treg and Th17 cells were detected by immunohistochemistry, RT-PCR, immunofluorescence, Western blot and flow cytometry. Phosphorylation levels of ERK1/2 and CREB were analysed. Results: The administration of SPRC significantly increased the expression of CSE in the gingival tissue and the concentration of endogenous H2S in the peripheral blood. Simultaneously, SPRC significantly inhibited the resorption of alveolar bone based on the H&E staining, micro-CT and methylene blue staining analysis. Compared with the periodontitis group, the levels of IL-17A, IL-10 were downregulated and IL-6,TGF-β1 were upregulated in the SPRC groups. In the SPRC group, the percentage of TH17 cells and the expression of ROR-γt were downregulated, while the percentage of Tregs and the expression of Foxp3 were upregulated accompanied with inhibition of phosphorylation ERK1/2 and CREB. Conclusion: SPRC can prevent the progression of periodontitis by regulating the Th17/Treg balance by inhibition of the ERK/CREB signalling pathway.